The Power of Deficit Discourses in Student Talk about Writing - Makmillen, Shurli; Norman, Kim (Discourse and Writing/Rédactologie, 2019)
Does engagement with writing centre consultants in one-on-one consultations help students shift from remedial discourses toward meta-cognitive awareness more in keeping with the nature of peer review in an academic setting? This study investigates this question through looking longitudinally over a four-year period in a Canadian university writing centre. We situate this research within wider discussions of Standard English and remediation in student academic writing, as well as writing centre research that explores correlations between numbers of writing centre visits and both students’ confidence as writers and their intrinsic motivation. Using a corpus-supported genre and discourse analysis, we focus on student appointment requests, as well as summative writing centre consultant notes. Results suggest that deficit discourses are highly tenacious, which we explain in part as the result of the constraints inherent in the genre of requests for help, and also in terms of the institutional positioning of writing centres.